Making Our Future : Visionary Folklore and Everyday Culture in Appalachia - Hilliard, Emily (University of North Carolina Press, 2022)
"In this book, Emily Hilliard draws from her work as state folklorist to explore contemporary folklife in West Virginia. In doing so, she challenges the common perception of both folklore and Appalachian culture as static, antiquated forms, offering instead the concept of 'visionary folklore' as a future-focused, materialist, and collaborative approach to cultural work"--